Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/coh.0000000000000237
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in HIV-1-mediated immunopathology

Abstract: Purpose of the review This article reviews our current knowledge regarding the role of sex and sex hormones in regulating innate immune responses to viral infections, which may account for the described sex differences in immunity to HIV-1. Recent findings Prominent sex differences exist in various infectious and autoimmune diseases. Biological mechanisms underlying these differences include the modulation of immunological pathways by sex hormones and gene dosage effects of immunomodulatory genes encoded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 71 publications
(86 reference statements)
1
33
1
2
Order By: Relevance
“…Meta-analysis data indicates 41% less HIV RNA in women compared to men following primary infection, which gradually increase to a higher viral load set point compared to males after chronic infection (149151). In females, HIV-1 promotes type 1 IFN production by pDCs via TLR7 signaling, which itself is increased downstream of E3 signaling (115, 152).…”
Section: Rna Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analysis data indicates 41% less HIV RNA in women compared to men following primary infection, which gradually increase to a higher viral load set point compared to males after chronic infection (149151). In females, HIV-1 promotes type 1 IFN production by pDCs via TLR7 signaling, which itself is increased downstream of E3 signaling (115, 152).…”
Section: Rna Virusesmentioning
confidence: 99%
“…Follow up studies have shown that even with same viral load pDCs obtained from females showed higher CD8+ T cell activation compared to men (115). Additionally, females mount a stronger B and T cell activation following HIV-1 infection due to higher baseline count of CD4 + T and CD8 + T cells in women as compared to men (115, 151). The concentration of estrogen binding SHBG is increased in HIV infected male individuals.…”
Section: Rna Virusesmentioning
confidence: 99%
“…Most human immunological studies during AHI have been done in resource-rich countries in patients infected with HIV subtype B, yet HIV-1 subtypes differ in their virulence [1,[23][24][25]. Also, the previous studies were mostly conducted in cohorts that were dominated by male patients, yet the highest burden of HIV in sub-Saharan Africa is in women, and gender has been shown to affect inflammatory responses [26]. Furthermore, geographical localization determines the basal inflammatory state due to environmental exposure to other endemic pathogens [27].…”
Section: Introductionmentioning
confidence: 99%
“…Interventions in NHP studies have elucidated the role of IFN and microbial translocation, although these studies may not always be reproducible in humans given the complexity of human infection with various comorbities, genetics and life style factors. Sex differences in innate immune sensing and IFN responses by pDCs can also have a critical role in determining differences in HIV-1 disease manifestations between women and men during acute and chronic infection, and require further studying [15]. Cardiovascular disease [16] and neurocognitive disease [17] represent important morbidities in treated patients with HIV-1 infection and have been linked to both adaptive and innate immune activation.…”
mentioning
confidence: 99%